Pengembangan Topik Basic Interactive Web untuk Pembelajaran Aplikasi Web Berbasis Node JS pada Platform iCLOP (Intellegent Computer-Assited Progamming Learning Platform) - Pratama, Muhammad Irgy; Syaifudin, Yan Watequlis; Hani’ah, Mamluatul (UNIVERSITAS SERAMBI MEKKAH, 2024)
One example of the use of web applications is E-Learning. The form of progress in the development of technology and information in the world of education is E-Learning. E-Learning is an innovation that has a huge contribution to the change of the learning process, where the learning process is no longer only listening to the description of the material from the lecturer but students also do other activities such as observing, demonstrating and others. In this study, we will focus on providing a system that can help students learn Website programming with the topic of Basic Interactive Web and integrate it with the iCLOP platform which can be accessed by students and lecturers to support the KBM process, especially in the lecture on website programming. Then, in this study, it can be concluded that the results of the system test to 40 students produced good results, the application could be used by 40 students successfully.